Carbohydrate gel ingestion and immunoendocrine responses to cycling in temperate and hot conditions - Peake, J. M.; Peiffer, J. J.; Abbiss, C. R.; Nosaka, K.; Laursen, P. B.; Suzuki, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
Purpose: Heat stress might attenuate the effects of carbohydrate on immunoendocrine responses to exercise by increasing endogenous glucose production and reducing the rate of exogenous carbohydrate oxidation. The authors compared the efficacy of carbohydrate consumption on immune responses to exercise in temperate vs. hot conditions. Methods: Ten male cyclists exercised on 2 separate occasions in temperate (18.1 ± 0.4 °C, 58% ± 8% relative humidity) and on another 2 occasions in hot conditions (32.2 ± 0.7 °C, 55% ± 2% relative humidity). On each occasion, the cyclists exercised in a fed state for 90 min at ~60% VO2max and then completed a 16.1-km time trial. Every 15 min during the first 90 min of exercise, they consumed 0.24 g/kg body mass of a carbohydrate or placebo gel. Results: Neutrophil counts increased during exercise in all trials (p < .05) and were significantly lower (40%, p = .006) after the carbohydrate than after the placebo trial in 32 °C. The concentrations of serum interleukin (IL)-6, IL-8, and IL-10 and plasma granulocyte-colony-stimulating factor, myeloperoxidase, and calprotectin also increased during exercise in all trials but did not differ significantly between the carbohydrate and placebo trials. Plasma norepinephrine concentration increased during exercise in all trials and was significantly higher (50%, p = .01) after the carbohydrate vs. the placebo trial in 32 °C. Conclusion: Carbohydrate ingestion attenuated neutrophil counts during exercise in hot conditions, whereas it had no effect on any other immune variables in either temperate or hot conditions.